Menjadi Entrepeneur Sukses : Strategi dan Maindset untuk Menghadapi Tantangan Diera Digital - Marni Marni; Yosia Belo; Patrisius Liber (Journal of Student Research, 2024)
Becoming a successful entrepreneur in the digital era is a journey filled with challenges and opportunities. In a rapidly changing business landscape, the ability to adapt to technological advancements and consumer behavior is key to success. This article explores the essential strategies and mindsets necessary for entrepreneurs to achieve success. The main focus is on four aspects: adaptive strategies, innovative mindsets, mastery of digital technology, and the development of a strong team. Adaptive strategies enable entrepreneurs to respond quickly to market changes, while an innovative mindset encourages them to view failures as learning opportunities. Mastery of digital technology enhances efficiency and competitiveness, and a committed, solid team fosters a positive work environment. Through continuous evaluation and adjustment of strategies, entrepreneurs can ensure the sustainability and growth of their businesses. This article serves as a guide for entrepreneurs to leverage challenges in the digital era as opportunities for innovation and long-term success.